2003
DOI: 10.1177/1362361303007002007
|View full text |Cite
|
Sign up to set email alerts
|

Social and Cardiac Responses of Young Children with Autism

Abstract: The behavioral and heart rate responses of 22 children with autism and 22 children with other developmental disabilities were compared whilst they were watching videotapes of a baby either playing or crying. We expected both groups to show arousal as increased heart rate when watching the video of the crying baby, and the children with autism to attend less than the other children to both videos. However, the children with autism were as attentive to the videos as the other children, and both groups showed hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(35 citation statements)
references
References 16 publications
2
33
0
Order By: Relevance
“…Children with symptoms of autonomic dysfunction also demonstrated higher levels of resting heart rate than the typical children. Earlier studies found differences in heart rate between children with autism and children with developmental delays, with developmentally delayed children displaying lower heart rate in the first 10 s after the experimenter showed distress (Corona et al 1998) and during the first 10 s of separation from mothers than during baseline (Sigman et al 2003). These two studies suggest that children with autism did not express an autonomic ''orienting response'' (i.e., decreased heart rate) or an ''aversive response'' (i.e., increased heart rate) to the distressed experimenter.…”
Section: Social Behavior and Autonomic Nervous Systemmentioning
confidence: 95%
“…Children with symptoms of autonomic dysfunction also demonstrated higher levels of resting heart rate than the typical children. Earlier studies found differences in heart rate between children with autism and children with developmental delays, with developmentally delayed children displaying lower heart rate in the first 10 s after the experimenter showed distress (Corona et al 1998) and during the first 10 s of separation from mothers than during baseline (Sigman et al 2003). These two studies suggest that children with autism did not express an autonomic ''orienting response'' (i.e., decreased heart rate) or an ''aversive response'' (i.e., increased heart rate) to the distressed experimenter.…”
Section: Social Behavior and Autonomic Nervous Systemmentioning
confidence: 95%
“…Cardiac responses have been used in typically developing children to analyze whether stimuli are aversive (heart rate acceleration) or interesting (slowing heart rate) (Eisenberg & Fabes, 1999;Fabes, Eisenberg, & Eisenbud, 1993;Sigman, Dissanayake, Corona, & Espinosa, 2003). Therefore, as a second physiological indicator of coping with stress, heart rate (HR) has also been examined in this study during the SSP.…”
Section: Introductionmentioning
confidence: 98%
“…The other person's affect thus seemed interesting to children with a developmental delay but not to children with autism. Sigman et al (2003) investigated the cardiac responses of children with autism and children with developmental delay to, among others, parental separation and reunion. They found that children with developmental delays showed lower heart rate during the first 10 s of separation than baseline, whereas children with autism did not show any orienting response.…”
Section: Introductionmentioning
confidence: 99%
“…More than 51% was gained by autistics in their social-emotional reorganization and 18% audio tone of Autistics had also improved after including video including facial emotion photographs [18]. Sigman et al had examined the crying and happy emotions of autistic and analyzed the change in their cardiac and attention responses during video stimuli [19]. The measured heart rate was also confirmed the interests and attraction responses of autistics as same to typically developed, but autistics had pretended ignored social behavior.…”
Section: Introductionmentioning
confidence: 90%